How much priority bonus should be given to registered organ donors? An experimental analysis - Annika Herr; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Recent laboratory experiments have demonstrated that prioritizing registered donors on the waiting list impressively increases the willingness to register as an organ donor. In these experiments, registered organ recipients are prioritized regardless of howlong they have been on thewaiting list. In the field, however, the willingness to register is only one factor affecting the waiting list. In this paper, we provide a comparative-statics analysis of the priority treatment by varying the number of bonus periods a registered person can skip on thewaiting list. We want to assess how much of a priority bonus registered persons should obtain in order for registration rates to improve. Our results indicate that a higher number of bonus periods significantly improves registration rates whereas a small bonus of only one period is of minor significance. A bonus of three periods ofwaiting time has the same effect as absolutely prioritizing registered recipients.
Keywords: C90; I10; I18; 330; organ donation; laboratory experiment; priority rule; waiting list